Changes in paleoceanography and methane release in relation to past climatic variability at Vestnesa Ridge, Svalbard - Åsheim, Jarl-Eirik Fløystad (UiT The Arctic University of Norway, 2017)
Sediment core HH16-549GC from Vestnesa Ridge in the Fram Strait, western Svalbard, has been investigated in order to reconstruct paleoceanographic and paleoclimatic conditions from 31,000 to 7500 cal years BP. Vestnesa Ridge is located in an area with extensive seepage of methane from the ocean floor. The core is retrieved from within a pockmark to reconstruct possible changes in seepage of methane in the past. Methane is a potent greenhouse gas regarded to be 25 times more potent than CO2. Fluctuations of methane release through time are particularly interesting to study in this area as the Fram Strait constitutes the predominant route for water and heat exchange between the world’s ocean and the Arctic Basin. Potential seepage of gas is important to study in order to investigate the possible effects it might cause on a continuously changing climate. The core has been divided into six different units based on lithological and stratigraphical parameters by investigating the distribution of grain sizes, magnetic susceptibility, assemblage of planktic and benthic foraminifera, stable isotopes and content of total carbon, total organic carbon, sulfur and calcium carbonate. An age model was established by correlating the results from HH16-549GC with results from a study from Jessen et al (2010), which compared and correlated 11 sediment cores from the western Svalbard region. The age model is based on AMS-14C dates and correlation to the Marine Isotope Stages (MIS) based on δ^18 O values from stable isotope analysis. The record covers MIS3 to MIS 1 (31,000-7500 cal years BP). Only late MIS3 from 31,000 to 29,000 cal years BP is present in this core and terminate at the end of Heinrich event 3 (30,500 cal years BP). MIS 2 is characterized by high δ^18 O values and comprises the period from 29,000 to 14,000 cal years BP which includes the Last Glacial Maximum (26,800-20,671 cal years BP), early deglaciation (20,671-19,327) and Heinrich event 1 (19,327-15,600 cal years BP). MIS 1 starts as the value of δ^18 O declines ...